Nanotúbulos en trypanosoma cruzi como mecanismo de resistencia al flujo (2021)
Trypanosoma cruzi is the etiological agent of Chagas disease, an important cause of infectious chronic myocardiopathy in Latin America. Parasite life cycle involves flagellated and non-flagellated forms, and two main hosts: a triatomine and a mammal. Epimastigotes are the flagellated forms inside the triatomine gut, those travel across the arthropod intestine until they mature (metacyclogenesis) into metacyclic trypomastigotes, the infective form for humans. However, it has been described the potential of epimastigotes to infect mammals, as well as epimastigote-like forms have been found inside cells. Movement of the parasites is towards the flagellum, and this is the structure that first adheres to host cells. Parasites must defy rough conditions inside host gut, particularly the shear stress generated by the intestine. Here, it is described how shear stress acts on and deforms T. cruzi epimastigotes. A parallel flow chamber in which epimastigotes were dispensed was used to subject these to different magnitudes of shear stress after attachment to the surface. The shear stress causes the emergence of nanotubules in adhered epimastigotes, and that their elongation was proportional to shear stress as well as reversible when flow stopped. Composition of the nanotubules is mainly membrane, as determined by fluorescence and mechanical properties. Multiple tethering was observed, and accounts for increased adhesion under large shear stresses, as well for reduced movement. We suggest the formation of membrane nanotubules is a mechanism of adherence to host cells that prevents premature detachment from the surface, limiting the effect of shear stress over the parasite, favoring the continuity of the parasiteþs life cycle.